Laser drilling of via micro-holes in single-crystal semiconductor substrates using a 1070 nm fibre laser with millisecond pulse widths - Maclean, Jessica O.; Hodson, Jonathan R.; Voisey, K.T. (SPIE, 2015)
Micro-machining of semiconductors is relevant to fabrication challenges within the semiconductor industry. For via holes for solar cells, laser drilling potentially avoids deep plasma etching which requires sophisticated equipment and corrosive, high purity gases. Other applications include backside loading of cold atoms into atom chips and ion traps for quantum physics research, for which holes through the semiconductor substrate are needed. Laser drilling, exploiting the melt ejection material removal mechanism, is used industrially for drilling hard to machine materials such as superalloys. Lasers of the kind used in this work typically form holes with diameters of 100’s of microns and depths of a few millimetres in metals. Laser drilling of semiconductors typically uses short pulses of UV or long wavelength IR to achieve holes as small as 50 microns. A combination of material processes occurs including laser absorption, heating, melting, vaporization with vapour and dust particle ejection and resolidification. An investigation using materials with different fundamental material parameters allows the suitability of any given laser for the processing of semiconductors to be determined. We report results on the characterization of via holes drilled using a 2000 W maximum power 1070 nm fibre laser with 1-20 ms pulses using single crystal silicon, gallium arsenide and sapphire. Holes were characterised in cross-section and plan view. Significantly, relatively long pulses were effective even for wide bandgap substrates which are nominally transparent at 1070 nm. Examination of drilled samples revealed holes had been successfully generated in all materials via melt ejection.